KOMUNIKASI LINGKUNGAN DALAM MENJAGA KEARIFAN LOKAL MENCOKOU IKAN LUBUK LARANGAN DI DESA TANJUNG BELIT KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR - Silmi Kaffah; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Local wisdom is one of the cultural heritages that exist in society in accordance with their respective regions which have been passed down from generation to generation in a community group within the area itself. The tradition of tepokou ikan lubuk ban is one of the local cultural wisdoms where the river is protected through rituals or in accordance with local customs. The tradition of raking lubuk prohibited fish aims to maintain the smoothness of the river and protect and protect the local fish in the river from becoming extinct. This research is located in Tanjung Belit Village, Kampar Kiri Hulu District, Kampar Regency. This study uses a qualitative research method with a  environmental communication  approach. The subjects of this study consisted of 6 (six) speech people in the village of Tanjung Belit from the village head, ninik mamak, tourism awareness groups and community leaders and the outside community who know the tradition of feeding the lubuk ban fish using purposive sampling technique. Data collection was carried out through interviews, observation and documentation. The results of this study indicate that the tradition of mending lubuk prohibited fish in the community of Tanjung Belit village is a local wisdom of the local culture which has become an annual tradition and an icon for the people of Tanjung Belit village. Environmental communication carried out by the community of Tanjung Belit village in maintaining local wisdom, namely Communication through the village government and Ninik Mamak, Communication through tradition and communication through customary law. Keywords : Enviromental Communication, Local Wisdom, Mencokou Ikan